2013
DOI: 10.3892/mmr.2013.1584
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine, a naturally occurring amino monosaccharide, inhibits A549 and H446 cell proliferation by blocking G1/S transition

Abstract: Abstract. Uncontrolled proliferation is important in tumorigenesis. In the present study, the effects of glucosamine on lung cancer cell proliferation were investigated. The expression of cyclin E, one of the key cyclins in the G1/S transition, and Skp2, the ubiquitin ligase subunit that targets the negative cell cycle regulator, p27 Kip1, were also assessed. Moreover, the underlying mechanisms of action of glucosamine were investigated in lung cancer cells. A549 and H446 cells were synchronized using thymidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Previous studies have reported that glucosamine inhibits cell growth [15,16] and cell-cycle progression [8,9,19] and induces apoptosis [20] in various cell lines. We therefore investigated whether the anti-cancer effect of glucosamine was associated with cell growth, cell-cycle arrest and apoptosis in NSCLC cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that glucosamine inhibits cell growth [15,16] and cell-cycle progression [8,9,19] and induces apoptosis [20] in various cell lines. We therefore investigated whether the anti-cancer effect of glucosamine was associated with cell growth, cell-cycle arrest and apoptosis in NSCLC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Results of a recent study indicated that glucosamine induces G1 cell-cycle arrest in mesangial cells and human cancer cells through a mechanism involving decreased expression of cyclin D1 and increased expression of p21 Waf1/Cip1 , which are positive and negative regulators of cell cycle progression, respectively [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some drugs that have cytotoxic effects on NSCLC also have obvious effects on SCLC, such as wentilactone A, which is cytotoxic to both H460 and H446 [16] , and glucosamine, which is cytotoxic to A549 and H446 cells [17] . Therefore, although there has been no report of the effect of EVO on SCLC to date, EVO may be a potential new drug candidate for the treatment of SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin E binds and activates the cell cycle-dependent protein kinase cyclin-dependent kinase 2 (CDK2) to promote transition of the cell cycle from G 1 to S phase ( 72 ). Increased expression of CDK2 can cause chromosomal instability and accelerate the occurrence of cancer ( 73 ).…”
Section: Substrates and Mechanisms Of Fbxw7 Involved In Tumor Suppresmentioning
confidence: 99%